Monitoring of landscape combinations and concourses in the Hungarian Danube‐bend - Csereklye, Erzsébet Krisztina (Journal of Environmental Engineering and Landscape Management, 2010)
In Hungarian Danube‐bend the flora of the area is very diversified due to climatic factors. Numerous species of flora characteristic of the area are under protection. The Danube‐bend and vicinity is one of the most well‐known part of Hungary, rich in historical relics and in natural assets. The city of Vác occupies a central place in the Danube‐Bend Region. Among Vác's attributes, we can find rare and invaluable cultural and historical values. The most significant natural attribute is the Grove of Vác near the Danube bank. The example of the Grove of Vác is of country‐wide importance in many aspects – it is part of the Duna‐Ipoly National Park – though local protection is reasonable regarding the treatment and links because of the pollution of the environment. The natural advantages are affected by air pollution due to the increased industrial, commercial, and economic life of the city. Nowadays, the research of environmental pollution comes to the front because of the importance of heavy metals in the landscape classification. Even though the heavy metals are a natural component of the environment, we have to look them toxic materials. This paper focuses on the pollution analysis I carried out with various plant samples. It shows the main toxicology pollutants present in different landscape combinations and concourses. In tree specie, like Salix alba, near the band of No. 2 motorway I observed 5–8 times more values as compared with samples from the Duna‐Ipoly National Park and nearly all kinds of heavy metals was elevated in Plantago major. In the life of the ecosystem, the primary source of heavy metals is the No. 2 motorway and the secondary is the pollution of the Danube bank.Aplinkos taršos įtakos kraštovaizdžiui Dunojaus vingyje Vengrijoje monitoringasSantrauka. Vengrijoje Dunojaus vingyje augalija dėl klimatinių veiksnių yra labai įvairi. Dauguma teritorijai būdingu augalijos rūšių saugomos. Dunojaus vingis ir apylinkės – viena iš geriausiai Vengrijoje žinomu vietų, turtingų istorinių relikviju ir gamtos vertybių. Vacas (Vác) – miestas, išsidėstęs centrinėje Dunojaus vingio regiono dalyje. Miestas turi retų ir neikainojamų kultūrinių ir istorinių vertybių. Reikšmingiausias natūralusis jo bruožas yra Vaco giraitė šalia Dunojaus kranto. Ji kraštui svarbi daugeliu aspektų – tai dalis Duna‐Ipoly nacionalinio parko. Čia taikoma vietinė apsauga, pagrįsta tvarkymu stebint aplinkos taršą, kuri daugiausiai pasireškia oro tarša dėl pramonės, komercinės ir ekonominės veiklos mieste. Šiais laikais aplinkos taršos tyrimai tampa vis aktualesni dėl besikaupiančių sunkiųjų metalų. Net jei sunkiųjų metalu šaltiniai gamtiniai, reikia stebėti, kad koncentracijos neviršytų leidžiamujų. Straipsnyje taršos analizė pateikiama įvairių augalų tyrimų pavyzdžiais. Tiriant medžius Salix alba, augančius šalia greitkelio Nr. 2 ruožo, buvo nustatytos 5–8 kartus didesnės teršalų koncentracijos, palyginti su nustatytomis Duna‐Ipoly nacionaliniame parke. Beveik visų sunkiųjų metalų koncentracijos buvo didesnės Plantago major. Tiriant ekosistemas nustatyta, kad pirminis sunkiųjų metalų šaltinis yra greitkelis Nr. 2, su tuo susijusi Dunojaus vingio tarša.Reikšminiai žodžiai: Dunojaus vingis, augalija, Vengrija, kraštovaizdžio ekologija, tarša.Мониторинг влияния загрязнения окружающей среды на ландшафт в изгибе Дуная в ВенгрииРезюме. Флора региона в изгибе Дуная в Венгрии весьма разнообразна в связи с климатическими факторами. Многие виды флоры, характерные для данной области, находятся под охраной. Этот регион является одним из наиболее известных в Венгрии. Он богат историческими реликвиями и природными достопримечательностями. Город Вац (Vác) занимает центральное место в регионе. Большое культурное и историческое значение присуще многим его достопримечательностям. Наиболее велико в природном отношении значение рощи в городе Вац на берегу Дуная. Роща города важна не только для края, но и для всей страны во многих отношениях. Это часть национального парка, значение которого неоценимо в связи с защитой окружающей среды от загрязнений, выделяемых промышленными, коммерческими и другими предприятиями. В настоящее время исследования загрязнения окружающей среды становятся все актуальнее в связи с необходимостью классифицировать тяжелые металлы по их воздействию на ландшафт. Даже тяжелые металлы, являющиеся естественным компонентом окружающей среды, могут расцениваться как токсичные элементы. В статье основное внимание уделяется анализу загрязнителей на примере их воздействия на разные растения. Проанализировано токсическое воздействие загрязнителей в разных их сочетаниях и в связи с особенностями ландшафта. В коре деревьев (Salix Alba), находящихся на участке вблизи скоростной автомагистрали № 2, было зафиксировано загрязнение металлами, в 5–8 раз превышающее подобные значения в национальном парке Дунай-Ипель. В жизни экосистемы первичным источником тяжелых металлов является автомагистраль № 2 и вторичным – загрязнения берегов Дуная.Ключевые слова: изгиб Дуная, флора, Венгрия, ландшафтная экология, загрязнение окружающей среды.First Published Online: 14 Oct 2010